TRANSFORMASI SISTEM IRIGASI SUBAK YANG BERLANDASKAN KONSEP TRI HITA KARANA - WAYAN WINDIA; SUPRODJO PUSPOSUTARDJO; NYOMAN SUTAWAN; PUTU SUDIRA; SIGIT SUPADMO ARIF (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Subak irrigation system beside as an appropriate technological system, but as acultural system as well. This fenomenon indicate that basically subak irrigationsystem is a technological system that has been developed as a part of cultural society.Because subak system is viewed as a technological system, so this system has anability to be transformed. Meanwhile, limitation of the ability of subak irrigationsystem to overcome the extreem conditions, basically can be solved through theharmony and togetherness, based on the Tri Hita Karana (THK) principles as a basicof subak system. Futhermore, through inverse technique, it can be seen the ability ofsubak system, that can be transformed. And then, through Fuzzy Set Theory, it can beseen the dominance or ranks of the all elements of subak system, which are also as aconsideration on the transformation process.